West of the American dream : an encounter with Texas - Christensen, Paul, 1943- (Tarleton State University southwestern studies in the humanities, 2001)
"Like many a pioneer exiting the eastern forests, Paul Christensen felt the strangeness of an alien landscape when he first arrived in Texas in 1974. Schooled in the cool colors of life and poetry in the urban East, he approached his new career in the Southwest with missionary zeal and purpose: to discover the land and the kind of people and poetry it produced."